How do foreign language teachers maintain their proficiency? A grounded theory investigation. (April 2016) - Valmori, Lorena; I. De Costa, Peter
Abstract: Building on Markus and Nurius's (1986) possible selves theory to investigate language teachers' engagement in professional development, this case study examines how nine Italian school foreign language (FL) teachers in two types of high schools (college preparation and vocational schools) experienced and responded to changes in their FL proficiency. Interview data, analyzed with a grounded theory approach, showed that when dealing with professional development, the FL teachers had to decide whether to (1) engage in professional development activities, and (2) maintain their engagement with or without a supportive community. Their decisions and engagement were influenced by the strength of the dissonance between the perception of their actual and possible L2 selves. The findings have implications for designing in-service professional development courses that take into consideration teachers' needs in relation to their school environments as FL teachers navigate the life-long experience of learning and maintaining a foreign language.